Festivalising! : theatrical events, politics and culture - Hauptfleisch, Temple (Themes in theatre ;, 2007)
Throughout the world festivals are growing - in numbers, in size, in significance - and serve as spaces where aesthetic encounters, religious and political celebrations, economic investments and public entertainment can take place. In this sense, festivals are theatrical events. This volume contains discussions of 14 diverse festival events from five continents across the globe, written by members of the IFTR/FIRT Working Group on the Theatrical Event, the same group that has produced the ground-breaking study Theatrical Events - Borders Dynamics Frames in 2004 (also published by Rodopi). The e.